Pengaruh Motivasi, Kompensasi dan Beban Kerja Terhadap Produktivitas Karyawan Anterja Gresik - Rafi Exa Fahrudi; Heru Baskoro (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The success of a company can be seen from the level of productivity of its employees. This study aims to determine the effect of motivation, compensation and workload on the productivity of Anteraja Gresik employees. This research method is quantitative and primary data is obtained using a questionnaire. The population of this study is Anteraja Gresik employees and a sample of 30 employees selected using the saturated sampling method. SPSS 23 software is used for data analysis and hypothesis testing. The results show that the motivation variable has a positive but insignificant effect on the productivity of Anterja Gresik employees. The compensation variable has a positive and significant effect on the productivity of Anterja Gresik employees. The workload variable has a negative but insignificant effect on the productivity of Anterja Gresik employees.